2022
DOI: 10.1038/s41598-022-17112-3
|View full text |Cite
|
Sign up to set email alerts
|

Novel compound shows in vivo anthelmintic activity in gerbils and sheep infected by Haemonchus contortus

Abstract: The control of gastrointestinal nematodes in livestock is becoming increasingly difficult due to the limited number of available drugs and the rapid development of anthelmintic resistance. Therefore, it is imperative to develop new anthelmintics that are effective against nematodes. Under this context, we tested the potential toxicity of three compounds in mice and their potential anthelmintic efficacy in Mongolian gerbils infected with Haemonchus contortus. The compounds were selected from previous in vitro e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Three out of these four derivatives (BZD46, BZD56, and BZD59) were also the most active compounds in the present study against F. hepatica . Another study reported that BZD58 (the 2-arylcarboxamido type II), administered at a dose of 120 mg/kg, exhibited in vivo efficacy of 95% in sheep infected with the gastrointestinal nematode Haemonchus contortus [ 22 ]. However, this compound displayed an ovicidal effect of less than 50% in Fasciola at a dose of 10 µM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation

New benzimidazole derivative compounds with in vitro fasciolicidal properties

Valderas-García,
Castilla-Gómez de Agüero,
González del Palacio
et al. 2024
Parasites Vectors
Self Cite
“…Three out of these four derivatives (BZD46, BZD56, and BZD59) were also the most active compounds in the present study against F. hepatica . Another study reported that BZD58 (the 2-arylcarboxamido type II), administered at a dose of 120 mg/kg, exhibited in vivo efficacy of 95% in sheep infected with the gastrointestinal nematode Haemonchus contortus [ 22 ]. However, this compound displayed an ovicidal effect of less than 50% in Fasciola at a dose of 10 µM.…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, the present study assessed the in vitro activity of a series of new benzimidazole derivatives (BZDs) against several stages of the trematode F. hepatica . Some of the tested compounds had previously demonstrated in vitro and in vivo activity against two gastrointestinal nematodes infecting ruminants: Teladorsagia circumcincta and Haemonchus contortus [ 20 22 ].…”
Section: Introductionmentioning
confidence: 99%

New benzimidazole derivative compounds with in vitro fasciolicidal properties

Valderas-García,
Castilla-Gómez de Agüero,
González del Palacio
et al. 2024
Parasites Vectors
Self Cite